Analisis Kinerja Keuangan Unit Pengelola Kegiatan (UPK) Simpan Pinjam Perempuan (SPP) Kecamatan Siulak Kabupaten Kerinci - Zachari Abdallah (Journal of Technopreneurship on Economics and Business Review, 2021)
This study aims to assess and analyze the financial performance of the women's savings and loan activity management unit (UPK-SPP), Siulak District, Kerinci Regency. The assessment of financial performance consists of two aspects, namely financial and loan management. This study uses secondary data derived from the financial statements of UPK SPP, Siulak District, Kerinci Regency, in the form of UPK income statements and other related reports from 2014 to 2018. The data were analyzed using the financial ratio analysis approach. The results showed that the financial performance of UPK SPP, Siulak District, Kerinci Regency, seen from the aspect of financial management from 2014 to 2018 ranging from 17.77% to 21.15% was included in the category of poor performance, while the financial performance of UPK SPP Siulak District, Kerinci Regency seen from the aspect of loan management from 2014 to 2018 ranged from interval 1.92%-2.52% is in the category of poor performance.. The results of the UPK SPP financial health assessment in Siulak District, Kerinci Regency from 2014 to 2018 were 61.66, including the adequate category.